PRINSIP-PRINSIP KONSERVASI LINGKUNGAN DI DALAM AL-QUR’AN - Hasan Ayatullah; Aldomi Putra; Nurbaiti (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
The global ecological crisis has sparked widespread debate about the human-nature relationship since the 1960s. Lynn White, Jr. criticized the anthropocentric tendencies in Judeo-Christian traditions, which he argued contributed to environmental degradation. In contrast, the principles of environmental conservation in the Qur’an remain underexplored. This study addresses this gap by examining ecological concepts in the Qur’an and their implications for environmental sustainability. Using a qualitative literature review methodology, we systematically analyze relevant Qur’anic verses and scientific interpretations to elucidate these principles. Our findings reveal two key concepts: first, the Qur’an integrates environmental stewardship with faith, asserting that true belief necessitates environmental responsibility. Second, the Qur’an designates humans as stewards (khalīfah) of the Earth, tasked with its wise management and care. This study contributes to the discourse on religion and ecology by highlighting the potential role of the Qur’an in promoting sustainable environmental practices